Wavelet coherence analysis of foF2 over Boulder station during different geomagnetic activity - Giri, Ashutosh; Adhikari, Binod; Shrestha, Bikash; Rimal, Shramik (Himalayan Physics, 2023)
A geomagnetic storm is a major disturbance of Earth’s magnetosphere that occurs when there is a very efficient exchange of energy from the solar wind into the space environment surrounding Earth. During solar and geomagnetic activities, critical frequency of F2 layer (foF2) varies in a great extent. The focus of the current study is on variations in foF2, the critical frequency of the F2 layer, during the intense geomagnetic storm of solar cycle 24 and quiet storm of solar cycle 25. The foF2 data of mid latitude station BC840 (Boulder) in the American region have been used to study geomagnetic and solar wind properties linked with foF2. Time series analysis and Wavelet Coherence analysis have been used to establish the relationship between those parameters. We have found considerable effect of solar and geomagnetic storm disturbances on foF2 during the geomagnetic storm time. The foF2 is enhanced prior to the storm and depletes during recovery phase with no significant changes observed during weak storm. The enhancement or depletion in foF2 may be used as precursor of geomagnetic storms. With long trend analysis and larger database we can make a catalog which can be used to predict the geomagnetic storm and deepen our understanding in impacts of storms on communication signals due to energy injected in ionosphere.